Assessing the Role of Opportunity and Low Self-Control in Juvenile Hacking. - Holt, Thomas J.; Cale, Jesse; Brewer, Russell; Goldsmith, Andrew (Crime & Delinquency, 2021)
Gottfredson and Hirschi's general theory of crime argues individuals with low self-control are more likely to engage in crime on and off-line. There is less research considering the role of opportunity, as low self-control should increase individuals' willingness to act on opportunities to offend. The importance of opportunity is distinct for cybercrime, as technology access may be differentially impacted by various demographic factors. This study surveyed 1,411 South Australian adolescents enrolled at secondary schools across a large metropolitan region to examine the relationships between opportunity and self-control for four forms of computer hacking. A series of binary logistic regression models illustrated that distinct opportunity factors and low self-control are associated with each form of hacking.